Gene-wide tagging study of the association between ABCC2, ABCC5 and ABCG2 genetic polymorphisms and multidrug resistance in epilepsy. (March 2011) - Kwan, Patrick; Wong, Virginia; Ng, Ping Wing; Lui, Colin Hiu Tung; Sin, Ngai Chuen; Wong, Ka Sing; Baum, Larry
Aim: To determine the association between polymorphisms of the multidrug transporter genes ABCC2, ABCC5 and ABCG2, and drug resistance in epilepsy by genotyping comprehensive sets of tagging SNPs.Materials & methods: A total of 25 tagging SNPs from ABCC2, ABCC5 and ABCG2 genes were genotyped in a total of 590 Han Chinese epilepsy patients (262 drug resistant and 328 drug responsive). Genotype and allele distributions in drug-responsive and drug-resistant patients were compared.Results: Genotype distributions of all the selected SNPs were consistent with Hardy––Weinberg equilibrium. None of the polymorphisms, either genotype or allele distributions, were significantly associated with drug resistance. For each gene, no haplotypes of over 1% frequency, and that included all SNPs of the gene, were associated with drug resistance.Conclusion: This gene-wide tagging study revealed no association between ABCC2, ABCC5 and ABCG2 genetic polymorphisms and multidrug resistance in epilepsy. Original submitted 11 August 2010; Revision submitted 5 November 2010.